Combination of tauroursodeoxycholic acid, co-enzyme Q10 and creatine demonstrates additive neuroprotective effects in in-vitro models of Parkinson’s disease - Alexander Shtilbans; Alexander Shtilbans; Wolfgang E. Reintsch; Valerio E. C. Piscopo; Andrea I. Krahn; Thomas M. Durcan (Frontiers in Neuroscience)
This study aimed to evaluate different combinations of three dietary supplements for potential additive or synergistic effects in an in vitro Parkinson’s Disease model. The complex and diverse processes leading to neurodegeneration in each patient with a neurodegenerative disorder cannot be effectively addressed by a single medication. Instead, various combinations of potentially neuroprotective agents targeting different disease mechanisms simultaneously may show improved additive or synergistic efficacy in slowing the disease progression and allowing the agents to be utilized at lower doses to minimize side effects. We evaluated four possible combinations of the three selected supplements: tauroursodeoxycholic acid (TUDCA), co-enzyme Q10 (CoQ10), and creatine, chosen for their effects on different targets that had previously shown neuroprotective effects in preclinical models. We evaluated the following combinations: (1) TUDCA+CoQ10, (2) TUDCA+Creatine, (3) CoQ10 + Creatine, and (4) TUDCA+CoQ10 + Creatine. We used induced pluripotent stem cell (iPSC) derived human dopaminergic neurons from a patient with Parkinson’s disease and healthy control, as well as microglial cells, to evaluate for an additive or synergistic effect of these combinations on neurodegeneration and neuroinflammation. We used neurofilament heavy chain, tubulin filament, and proinflammatory cytokines as metrics. We have identified a triple combination of these supplements that showed an additive protective effect across all these endpoints. Indeed, the agents in that combination could address the majority of the known pathways leading to neurodegeneration, such as accumulation of misfolded α-synuclein, mitochondrial dysfunction, reactive oxygen species, and neuroinflammation. We demonstrated that the combination of TUDCA, CoQ10, and creatine exerts an additive effect in in vitro models of a neurodegenerative disease, surpassing the efficacy of each compound individually. This combination shows strong potential as a candidate for further preclinical confirmatory studies and clinical trials as a neuroprotective treatment for patients with, or at risk for, Parkinson’s disease.